Influencia de la familia en el transtorno negativista desafiante en niños entre 5 y 11 años que asiten a consulta psicológica en el hospital Manuel Ygnacio Monteros Valdivieso IESS de la ciudad de Loja durante el periodo mayo-noviembre del 2013 - Plaza Granda, Lilian Gabriela (2014)
This research work aims to systematically relate to family dysfunction with oppositional defiant disorder, this is a cross-sectional study, descriptive, analytical cut the same that occurs within a quantitative approach; the sample was taken 60 children between 5 and 11 years old who attended the area of psychological inquiry in Manuel Ygnacio Monteros (IEES) Hospital of the city of Loja. The information obtained from children and parents came through the use of techniques and instruments such as observation and medical history, and application of psychological reagents: HTP, and Test of the Family. Among the main results is determined that patients previously diagnosed with oppositional defiant disorder mostly come from dysfunctional families, dysfunctional considering this dimension as the main risk factor for the development of this disorder, also symptoms that are evident with more frequently in these children are; inferiority feelings, difficulty contacting the environment, lack of stability and support among others. This thesis finds that family dysfunction affects whether the presence of symptoms of oppositional defiant disorder according to endorse the percentages obtained in this study. KEYWORDS: Oppositional Defiant Disorder, Family Dysfunction.